THE DEVELOPMENT OF FINE MOTOR AND VISUAL MOTOR SKILLS OF CHILDREN 4-5 YEARS OLD TO GET READY WRITE - Neneng Alawiyah; Naila Attamim (JECIES: Journal of Early Childhood Islamic Education Study, 2020)
The objective of this research is to describe: (1) the process development  of fine motor and visual motor skills of children 4-5 years old, (2) the learning media applied   development of  fine motor and visual motor skills, (3) the learning method applied development of  fine motor and visual motor skills of children 4-5 years old, (4) the learning evaluative applied development of fine motor and visual motor skills of children 4-5 years old to get ready write. The research is implemented at TK A “Plus” Insan Sejati, Cibinong West Java. This study is naturalistic qualitative deskriptive. The process of the research follows the Spradley’s advance stages which consists of collecting data by applying observation, interview, and documentation. Data analysis consists of domain analysis, taxonomi analysis, component analysis, and theme analysis. The result of the study show that: (1) the learning activities on the development fine motor and visual motor skills to get ready write are carried out by defference activities applied in each learning process, (2) learning strategy applied by the theacher are: defferent method, media and evaluation.Keywords: Early childhood, Development motor skills, Visual motor skills. ABSTRAKTujuan penelitian ini adalah untuk (1) memahami proses perkembangan keterampilan motorik halus dan visual motorik usia 4-5 tahun, (2) menemukan media yang digunakan dalam pengembangan keterampilan motoirk halus dan visual motorik dalam menyiapkan menulis, (3) mengetahui aplikasi metode yang digunakan dalam upaya pengembangan keterampilan motorik halus dan visual motorik usia 4-5 tahun, dan (4) penggunaan evaluasi dalam mengembangkan keterampilan motorik halus dan visual motorik usia 4-5 atahun dalam menyiiapkan menulis. Penelitian ini di laksanakan di TK A ”Plus” Insan Sejati Cibinong dengan menggunakan metode deskriptif kualitatif naturalistik. Proses penelitian ini mengikuti alur maju bertahap dari Spradley, proses pengumpulan data meliputi: analisis domain, analisis taksonomi, analisis komponen, dan analisis tema. Hasil penelitian menunjukkan bahwa: (1) pembelajaran dalam pengembangan keterampilan motorik halus dan visual motorik dalam menyiapkan menulis dilakukan melalui kegiatan-kegiatan yang beragam yang dilakukan pada setiap proses pembelajaran, (2) strategi pembelajaran yang digunakan meliputi: metode yang bervariasi, media yang disesuaikan dengan jenis kegiatan, dan evaluasi yang dilakukan pada setiap akhir kegiatan